CONTINUOUS FLOW PERITONEAL DIALYSIS IN A PREMATURE INFANT (A CASE REPORT) - Алексей Анатольевич Задворнов; Артем Александрович Черных; Евгений Валерьевич Григорьев; Мария Федоровна Семенова (The Publishing House Medicine and Enlightenment, 2021)
The article describes a case of continuous flow peritoneal dialysis in a premature baby with a very low body weight. It describes the course of the disease in a newborn before the acute renal damage onset, the technical equipment and consumables. Documentation of peritoneal dialysis is also presented. Despite the unfavorable outcome of the disease due to severe intraventricular hemorrhage, peritoneal dialysis was evaluated as successful. The child has stopped hyperkalemia and achieved a negative fluid balance. A wide range of studies are required to investigate various aspects of the use of peritoneal dialysis in premature infants.